2019
DOI: 10.3389/fpubh.2019.00157
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Tinnitus Treatment: An Exploratory Study Based on Internet Crowdsensing

Abstract: Introduction: Chronic tinnitus is a condition estimated to affect 10–15% of the population. No treatment has shown efficacy in randomized clinical trials to reliably and effectively suppress the phantom perceptions, and little is known why patients react differently to the same treatments. Tinnitus heterogeneity may play a central role in treatment response, but no study has tried to capture tinnitus heterogeneity in terms of treatment response. Research Goals: To test if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…There is a pressing need to standardize the use of VBM when evaluating tinnitus patients (Scott-Wittenborn et al, 2017). We should pay further attention to tinnitus heterogeneity, which could be expressed in terms of treatment response (Simoes et al, 2019). Research using machine learning may be helpful.…”
Section: Limitationsmentioning
confidence: 99%
“…There is a pressing need to standardize the use of VBM when evaluating tinnitus patients (Scott-Wittenborn et al, 2017). We should pay further attention to tinnitus heterogeneity, which could be expressed in terms of treatment response (Simoes et al, 2019). Research using machine learning may be helpful.…”
Section: Limitationsmentioning
confidence: 99%
“…This could be attributed to statistical variance, but it could also be claimed that some therapeutic interventions could potentially be beneficial in a specific subgroup of patients with identifiable characteristics. Very few studies, however, attempt to create and identify a certain profile correlating with treatment response and the main research question is limited to whether an intervention is effective or not in a group of patients, rather than which factors influence treatment response [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of tinnitus has been estimated between 10 and 15% in the adult population. From those, 20% will require clinical intervention and 80% are not particularly bothered by tinnitus [ 3 , 4 ]. Previous studies have shown that chronic tinnitus may be accompanied by comorbidities such as anxiety, depression and insomnia, and can have a negative impact on sleep quality, in a sense that the increased severity of sleep disruption is associated with increased tinnitus severity [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%